Psychological compatibility and its relationship to learning basic motor skills in handball among secondary school students through physical education and sports classes - faid, abdrazek (sports creativity, 2025)
This study aims to reveal the relationship between psychological adjustment and the learning of basic handball motor skills among secondary school students through physical education classes. The field study was conducted in several secondary schools in the M'Sila province. To achieve this objective, the researcher considered three dimensions of psychological adjustment: the adolescent's self-reliance, their sense of self-worth, and their feeling of freedom. Given the nature of the topic, the researcher adopted a descriptive approach, which is appropriate for the subject matter. The second part of the Mahmoud Attia Hanaa Personality Test, which focuses on psychological adjustment, was also used. For basic handball motor skills, the researcher used an assessment rubric approved by the Ministry of National Education. The study was conducted on a simple random sample of 330 students from several secondary schools in the M'Sila province. The results showed a positive correlation between the adolescent's self-reliance, sense of self-worth, and feeling of freedom, on the one hand, and the learning of basic handball motor skills, on the other. In other words, there is a positive correlation between psychological adjustment and the learning of basic handball motor skills.